Участие Слободских гусарских полков в русско-турецкой войне 1768–1774 гг. - Желтобородов, А. Н. (Давнина. Харківський історико-археологічний щорічник, 2016)
SummaryA. Zheltoborodov. The Participation of Slobodskiy Gusar Regiments in the Russian-Turkish War of 1768–1774In the article the participation of Ahtirskiy, Izumskiy, Ostrogozskiy, Sumskiy and Kharkov regiments in the Russian-Turkish War of 1768–1774 are described, the orders which were completed by gusar regiments during war actions are explained. Besides that Slobodskiy Gusar took part in fights and battles with Turkish forces they were drawn in reconnaissance, sentry post and patrol services.In the article the conclusion that Slobodskiy Gusar regiments reforming from the Cossacks ones standed the test by war successfully is made. The range of the battle tasks increased. The  training of Gusar regiments of actions on the battle area in the close orders allowed them always to win a victory over numerous Turkish irregular cavalry.